R-scale for pulmonary fibrosis: a simple, visual tool for the assessment of health-related quality of life - Scallan, Ciaran; Strand, Lauren; Hayes, Jennifer; Kadura, Suha; Collins, Bridget; Ho, Lawrence; Spada, Carolyn; Canestaro, Will; Kolb, Martin; Raghu, Ganesh (The European respiratory journal, 2022)
Patients with idiopathic pulmonary fibrosis (IPF) experience impaired health-related quality of life (HRQoL). Several tools have been developed to objectively assess HRQoL in this patient population, but none are in use in routine clinical practice. To develop a rapid, specific tool that can be used for patients with IPF during routine clinic visits. A novel and simple five-item numerical rating scale was developed and compared with two other previously validated tools. 100 consecutive patients with IPF managed at a centre for interstitial lung disease were recruited to complete the Raghu scale for pulmonary fibrosis (R-Scale-PF), King's Brief Interstitial Lung Disease questionnaire (K-BILD), and the EuroQol Five-Dimensional Five-Level questionnaire (EQ-5D-5L) in addition to pulmonary function and 6-min walk tests. All 100 patients successfully completed the three HRQoL tools with 53 completing them again at follow-up visits. Internal consistency was high (Cronbach's α 0.825) with minimal floor/ceiling effect. Concurrent validity of the R-Scale-PF was moderate to high compared with the K-BILD ( =-0.713) and the EQ-5D-5L ( =-0.665). Concurrent validity was moderate with physiologic measures (forced vital capacity, =-0.307, 6-min walking distance, =-0.383). The R-Scale-PF demonstrated good known-groups validity when comparing scores across stages of disease severity. The R-Scale-PF correlates well with the K-BILD and EQ-5D-5L. It is hoped that this novel simple numerical rating scale tool, subject to validation in patients from other centres, will provide an opportunity to objectively measure HRQoL in routine clinical practice for patients with IPF.